Resistência de união na interface cimento/dentina diante diferentes protocolos de irrigação final do espaço para pino - Andrade, Carla Frehner (2017)
Fiberglass posts have frequently been indicated for the reconstruction of teeth endodontically treated with a big loss of coronary structure, because besides of having a more favorable aesthetic, it increase the resistance of the restoration and allows the teeth to be restored more conservatively. The objective of the present study was to evaluate the bond strength at the cement / dentin interface in the post space after the samples were treated with 4 different final irrigation protocols followed by cementation with dual resin cement (Allcem Core - FGM). 48 human uniradicular premolars were used, which were divided into 4 groups (n = 12): Distilled Water Group (Control), NaOCl 2.5% + EDTA 17% Group, NaOCl 2.5% + Passive ultrasonic irrigation (PUI) Group and Solution of Chlorhexidine 2% Group. The pull-out test was performed and the results were submitted to the Anova test with paired comparisons of Tukey, at the level of five percent (5%) of significance. The NaOCl 2.5% + PUI group presented the highest bond strength. On the other hand, the Chlorhexidine group had besides of the lower union resistance, a greater number of flaws in the interface studied. It was concluded that the irrigation protocol for cleaning after post space preparation directly influences the bond strength at the cement / dentin interface.